Frequency of abnormal platelet indices among women presenting with preeclampsia - Khushboo, Khushboo; Asma, Asma; Naz, Tabassum; Benish, Benish; Mehmoodah, Mehmoodah; Parveen, Tooba (Journal of Neonatal Surgery, 2025)
Objective: To determine the Frequency of abnormal platelet indices among women presenting with preeclampsia Material and methods: This descriptive cross sectional study was conducted in duration of six months from 20-02-2017 to 19-08-2017, at Department of Obstetrics and Gynaecology Unit III, Shaheed Mohtarma Benazir Bhutto Medical University, Larkana. In total 95 women of age 18-40 years, having pregnancy 20 to 40 weeks, alive singleton fetus and confirmed preeclampsia were included. Patients with history of chronic hypertension, Idiopathic Thromobocytopenic Purpura, using anticoagulant drugs within last one month, multiple gestation and morbid obesity were excluded. Mean + SD, frequencies & percentages were calculated. Chi-square was used as test of significance with a P value <0.05 as significant. Results: Mean ± SD age of patients was 29.52 ± 6.17 years (Range 18 to 40). Mean ± SD parity was 1.71 ± 1.11 children (Range 1-4). Mean ± SD gestational age was 30.39 ± 4.90 weeks (Range 21-38). The mean platelet volume was 12.80 ± 6.82 fl, mean platelet count in mm3 was 2,22,997 ± 1,00,093 while mean platelet distribution width was 11.05 ± 5.95 fl. Thrombocytopenia was found positive among 32.6%. Frequency of abnormal platelet indices was 22.11% (n = 21). Conclusion: Preeclampsia is very dangerous condition posing life threat to mother and the fetus. The current study found that platelet volume and platelet distribution width both increase while platelet count decreases among women who develop the preeclampsia..